Application Design of Magic Words to Learn Reading for the First Grade Students at Elementary School using Kodular Website - Isnani, Salsabila Nurhaliza Putri; Rahmawati, Fitri; Hasanudin, Cahyo; Fitrianingsih, Ayu; Rahmawati, Oktha Ika; Chamalah, Evi (IKIP PGRI Bojonegoro, 2025)
Kodular is a web-based platform that provides a variety of features for creating Android applications. Its function is very similar to MIT App Inventor, with the main purpose of making Android application development easier. The purpose of this research is to develop an online learning application that can be accessed through Android-based smartphone. This application is designed using the Kodular platform and developed through the SDLC method of the Waterfall model, which includes the stages of need, design, implementation, verification, and maintenance. The results of the discussion of this research are the components that make up the screen display of the magic words application: learning to read which includes: 1) start page display, 2) introduction menu page display, 3) main menu page display, 4) introduction menu display, 5) quiz menu display, 6) menu display about the application. The conclusion of this research is that there are 5 stages in making the magic words application: learning to read using a codular website